2021
DOI: 10.29052/2413-4252.v7.i1.2021.26-31
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcome in adolescent and adult primigravida

Abstract: Background: Improving maternal and child health is prioritized globally; however, adolescent pregnancies remain the prime one among the many obstacles. The study aimed to determine the maternal and perinatal outcomes in adolescent and adult primigravida. Methodology: This cross-sectional study was carried out between 1st December 2018 to 30th November 2019, over a sample of 487 pregnant women (primigravida), presenting at the Jinnah Medical College Hospital, Karachi, for childbirth/delivery. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Early marriage, poor educational levels, low levels of sexual education and contraceptive use, and a high prevalence of poverty are all key variables in the rate of adolescent pregnancy in some traditional rural communities 3 . Adolescent pregnancy is typically seen as a high-risk group, with implications not only for the mother's emotions, education, and financial condition, but also for the mother's, child's, and community's health as a whole 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early marriage, poor educational levels, low levels of sexual education and contraceptive use, and a high prevalence of poverty are all key variables in the rate of adolescent pregnancy in some traditional rural communities 3 . Adolescent pregnancy is typically seen as a high-risk group, with implications not only for the mother's emotions, education, and financial condition, but also for the mother's, child's, and community's health as a whole 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Because MUAC has been shown to be closely related to maternal weight in studies, it has been suggested as a useful tool for screening maternal nutrition status and as a potential indicator of low birth weight (LBW), neonatal mortality, and morbidity, when weighing pregnant women is not possible 15 . Few studies focused on the detection of the best anthropometric indicators as predictors of pregnancy outcomes with greater sensitivity, specificity, and accuracy 4 .…”
Section: Introductionmentioning
confidence: 99%